Criticism of the Report of Bayt Zul-Aqfal in the Conquest of Toledo - Sohrab Eslami; Younes Farahmand (تاریخ اسلام)
The conquest of Andalusia was completed during the caliphate of Walid bin Abdul Malik (86-96 A. H) and under the leadership of Musa bin Nasir (19-97 A. H) and Tariq bin Ziyad (101-50 A. H) during the years 92-95 A. H. As a result of this conquest, many tribes entered Andalusia. This article examines the report of Bayt Zul-Aqfal in Toledo aiming the how of different ethnic groups entering Andalusia and their influence in compiling historical reports.The findings of the research done through the descriptive-analytical method and analysis of historical documents, show that the conquest of Andalusia and the new ethnic and cultural composition of the inhabitants of this region led to the fictional stories and narratives taken from the historical culture of these people were added to the historiography of Andalusia. Therefore, the report of Bayt Zul-Aqfal in the conquest of Toledo is one of the fabricated narratives of the conquest of Andalusia, the story of which arosed from this cultural mixture and found its way into the historical sources.